Addressing Diversity, Equity, and Inclusion in Environmental Engineering Education: A Review of Strategies - Gani, Paran; Jusoh, Muhammad Noor Hazwan; Hadibarata, Tony; Lai, Wai Yan; Yong, Leong Kong; Malang, Jameson; Ujan, Nancy; Hua, Ang Kean; Matias-Peralta, Hazel Monica (Tecno Scientifica Publisher, 2025)
While environmental engineering helps to solve major world challenges, it still struggles with diversity, equity and inclusion (DEI). This study seeks to understand the current progress of DEI in environmental engineering education at the university level and for professionals. It analyzes studies related to DEI to discover difficulties that hinder its integration and considers proposed solutions for promoting an inclusive environment. Some main obstacles are the low number of minorities, insufficient DEI information in courses and opposition to reform within institutions. Various promising ways such as making changes to the curriculum, inclusive teaching, student mentorship schemes, instructor development and community involvement are covered. Even so, these different approaches often miss proper support and coordination which reduces their usefulness over time. The review points out flaws in how assessment is done and suggests incorporating DEI concepts throughout education policies, teaching activities and professional life. In the end, it recommends ways that teachers, schools and policy groups can promote DEI by staying committed and joining forces.